Limitations in Ankle Dorsiflexion Range of Motion, Gait, and Walking Efficiency in Childhood Cancer Survivors. Issue 2 (March 2016) - Beulertz, Julia; Bloch, Wilhelm; Prokop, Aram; Rustler, Vanessa; Fitzen, Christina; Herich, Lena; Streckmann, Fiona; Baumann, Freerk T.
Abstract : Background: Improvements in survival rates in pediatric oncology have resulted in a growing need to identify adverse effects and improve rehabilitation in this population. Objective: This cross-sectional study aimed to investigate active ankle dorsiflexion (DF) range of motion (ROM), gait, walking efficiency, and motor performance in a mixed childhood cancer survivor population in comparison to healthy peers. Methods: Active ankle DF-ROM (goniometer), gait (Microgate Optogait 2D Gait Analysis), walking efficiency (6-minute walk test), and motor performance (German Motor Test 6–18) were assessed in a mixed childhood cancer survivor population after cessation of medical treatment (n = 13) in comparison to healthy children matched for age and gender (n = 13). Results: Active ankle DF-ROM, gait (stance, swing, and preswing phase), and walking efficiency were significantly impaired in survivors compared with control subjects. No significant difference between groups was found in motor performance. Conclusion: Despite sufficient total motor performance levels, specific limitations in physical functioning were identified in a mixed childhood cancer survivor sample. This highlights the importance of the present findings. Implication for Practice: The results from this study highlight the potential significance of limited ankle DF function, inhibited gait, and reduced walking efficiency as adverse effects of various types of childhood cancer. It is hoped this enhanced recognition by pediatric cancer patients, parents, and exercise professionals will initiate specific supportive strategies and potentially prevent further limitations.